Pengaruh Pelaksanaan Kursus Pra Nikah Terhadap Menurunnya Angka Perceraian Studi Kasus Di Kecamatan SINE Kabupaten Ngawi - Marwan Joni Mustaqim; Abdul Rouf (FAI- Undar, 2021)
The discussion about the pre-wedding course conducted by the Sine District KUA is a new thing. Family problems that occur in the community have caused the government, especially from the Ministry of Religion, to take the initiative to implement the program to improve the quality of good families and are expected to form sakinah, mawaddah and rahmah families. This program is implemented based on several strong reasons and accurate data for community development, especially in the family sphere. Looking back at the Government Regulations and Decrees of the Minister of Religion and laws, the high incidence of domestic violence, the high divorce rate, and the lack of public attention to health are the main reasons why this pre-marital course program is implemented. The most important thing is that people understand and know what is most important about a marriage and the real goals of marriage, and if the noble goals of marriage according to Islam are carried out, a family that is sakinah, mawaddah and rahmah will be formed. The compiler analyzes the data that has been collected using an inductive method, namely drawing conclusions starting from general knowledge of the course and marriage, and starting from this general knowledge, they want to assess a special event, namely the implications obtained from the pre-wedding course program. The sociological, psychological and historical approach is an approach used to examine a problem by linking a situation that exists in society as well as history or past events and the nature or character of that society in general. This type of research is field research by conducting observations, interviews and collecting some important data that can support the validity of this research. After the research was conducted, it was concluded that the pre-marital course provides positive value and contributes more to society to make a family sakinah, mawaddah and rahmah.